1981
DOI: 10.3758/bf03196963
|View full text |Cite
|
Sign up to set email alerts
|

Memory processing of spatial order as transmitted by auditory information in the absence of visual cues

Abstract: Two experiments were conducted concerning spatial order recall when spatial information is transmitted by auditory stimuli. Temporal order either was congruent with spatial order or was independent of spatial order. In Experiment 1, the comparisons were among normally or partially sighted subjects allowed to look, normally sighted subjects who were blindfolded, and blind children. The main findings were a superiority of the sighted subjects allowed to look (that is, to support auditory information with visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1984
1984
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Although learning and memory for visually specified positions or object locations has been investigated (e.g., Musen 1966;Pezdek et al 1986;Naveh-Benjamin 1987;Tresch et al 1993;Postma and De Haan 1996;Chieffi and Allport 1997), little research compares learning and memory performance in 3D space across modalities (e.g., Battacchi et al 1981). Recently, Loomis et al (2002) demonstrated that spoken language could produce a spatial representation that functioned behaviorally like one derived from 3D sound, despite the fact that the neural pathways to spatial representation are quite different across these input modalities.…”
mentioning
confidence: 99%
“…Although learning and memory for visually specified positions or object locations has been investigated (e.g., Musen 1966;Pezdek et al 1986;Naveh-Benjamin 1987;Tresch et al 1993;Postma and De Haan 1996;Chieffi and Allport 1997), little research compares learning and memory performance in 3D space across modalities (e.g., Battacchi et al 1981). Recently, Loomis et al (2002) demonstrated that spoken language could produce a spatial representation that functioned behaviorally like one derived from 3D sound, despite the fact that the neural pathways to spatial representation are quite different across these input modalities.…”
mentioning
confidence: 99%
“…For example, in an experiment that manipulated both presentation mode and the time span of recall, Jensen (1971) found that recall-performance varied for visual and auditory mode subjects. Following from Jensen, among others (e.g., Sperling, 1960; Haber & Standing, 1969; Wickelgren, 1969), recent research has focused on a variety of issues within individual presentation modes (rather than across modes), including the effect of alternative information processing models on auditory memory performance (Geiselman, Woodward, & Beatty, 1982) and spatial order processing in the absence of visual cues (Battachi, Franza, & Pani, 1982).…”
mentioning
confidence: 99%